Relationship Between Flexed Posture, Physical Performance and the Functional Status Level in the Elderly - Halfi Farmasari; Wanarani Alwin (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives : To provide a description of the severity of flexed posture, physical performance and functional status level in the elderly and to investgate the relationship between flexed posture (FP),physical performance and the functional status level in the elderly.Methods : One hundred and eight elders (60-90 year-old) with flexed posture were assesed in Geriatric and Physical Medicine and Rehabilitation Outpatient Clinics Hasan Sadikin Hospital Bandung from July until August 2010. Clinical assessment included the severity of FP( standing occipital to wall distance - OWD, demographic (age, gender, education, marital status, occupation), Body Mass Index (BMI), clinical profile(Mini-Mental State examination, Geriatric Depression Scale), Physical performance ( Short Physical Performance Battery – SPPB) and evaluation of disability ( Barthel index and Nottingham Extended Activities of Daily Living index - NADL index ) Study design is: crosssectional study.Results : The mean age of the subjects was 72.21 (6.69) and 68 (63.0%) were women. The severity of FP was classified as mild in 31 (28.7%), moderate in 50 (46.3%) and severe in 27 patients (25.05%).Physical performance was measured by SPPB median 8 (3-12). Disability or functional status level were measured by the Barthel index median 95 (65-100) and NADL index median 53 (12-63). The severe FP group was significantly different the from mild and moderate group in the clinical profile (greater depression and MMSE). Increased severity of FP was related to decline physical performance(SPPB)( p<0.001) and disability, Barthel index (p<0.001) and NADL index (p<0.001) in the elderly.Conclusions : Severity of flexed posture is realted to declined physical performance and functional status level in elderly.Keywords: Elderly, Flexed posture, SPPB, Barthel index, NADL index.